Integrable Degenerate E-Models from 4d Chern–Simons Theory - Liniado, Joaquin (2023)
We present a general construction of integrable degenerate -models on a 2d manifold using the formalism of Costello and Yamazaki based on 4d Chern–Simons theory on . We begin with a physically motivated review of the mathematical results of Benini et al. (Commun Math Phys 389(3):1417–1443, 2022. https://doi.org/10.1007/s00220-021-04304-7) where a unifying 2d action was obtained from 4d Chern–Simons theory which depends on a pair of 2d fields h and on subject to a constraint and with depending rationally on the complex coordinate on . When the meromorphic 1-form entering the action of 4d Chern–Simons theory is required to have a double pole at infinity, the constraint between h and was solved in Lacroix and Vicedo (SIGMA 17:058, 2021. https://doi.org/10.3842/SIGMA.2021.058) to obtain integrable non-degenerate -models. We extend the latter approach to the most general setting of an arbitrary 1-form and obtain integrable degenerate -models. To illustrate the procedure, we reproduce two well-known examples of integrable degenerate -models: the pseudo-dual of the principal chiral model and the bi-Yang-Baxter -model.